Recognition, relevance and renewal: reframing perspectives on entrepreneurship and networking through Aboriginal worldviews - Fort, Warrick Nerehana (Curtin University, 2017)
This thesis examines the influence of ontology on the theorisation and practice of entrepreneurship and networking. Research was conducted through in-depth interviews, most of which were undertaken with Aboriginal entrepreneurs, two literature reviews, participant observation, and a field journal. Research findings contribute to a ‘grander narrative’ of entrepreneurship, which recognises how entrepreneurship continues to be practised in a variety of settings and by a range of people whose ontologies have been marginalised within capitalist societies.